Effectiveness of individual health education on the practice of dengue fever prevention in an urban area of Puducherry, India - Saurabh, Suman; M, Veerakumar A; S, Kalaiselvi; C, Palanivel (Indian Journal of Community Health, 2014)
Background: Prevention of breeding of Aedes mosquito is an effective method for dengue control. Practice of source reduction to prevent breeding depends on the knowledge of the community, which can be improved by health education. Objectives: Our objective was to ascertain the knowledge and practice of the community regarding dengue and its prevention, and to assess the effectiveness of individual health education on practice of dengue prevention. Methodology: In urban service area of JIPMER, using Street-wise cluster sampling pre and post intervention data collection was done. Intervention was “Individual health education on the practice of dengue prevention”. Main outcome measures were Awareness and practice regarding dengue prevention. McNemar’s test was used in the analysis. Results: A total of 351 respondents were studied of whom 89% knew that dengue was spread by mosquitoes. Only one-fourths knew about the correct biting time and breeding condition of Aedes mosquitoes. Practice regarding draining of unused tyres, coolers, flower vases, disposal of coconut shells and keeping unused flower pots upturned were found to improve significantly after health education. Conclusions: Individual health education was effective in improving the practice of source reduction in a community with poor knowledge of vector biting and breeding habits.